PEMANFAATAN PANAS BUANG PADA EXHAUST PIPE SEPEDA MOTOR UNTUK PEMBANGKITAN ENERGI LISTRIK MENGGUNAKAN GENERATOR THERMOELEKTRIK - , Sugiyanto, ST, Prof. Dr.ing. Ir. Harwin Saptoadi, M.SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Motorcycle engine as SI (spark ignition) engine is about 40% of the energy of combustion is wasted as heat in the exhaust system. Utilizing waste heat is a form of alternative electric energy generation, besides that in the future is a significant opportunity to improve the efficiency of engines as well as decreased fuel consumption. One step to the utilization of waste heat is direct converting it into electrical energy using thermoelectric generator (TEG). Thermoelectric Generator Module made from Bismuth Telluride was chosen to convert waste heat in the exhaust pipe of Suzuki motorcycles FD 110 cc and FXR 150 cc. These modules are placed in three-point on the exhaust pipe, which is the first near the exhaust manifold, the second between the exhaust manifold and collector and third near the collector. Engine speed is taken at idle and 3000 rpm as the variations in electrical potential measurements without load. Electrical power is obtained by connecting in series three test points then connected with a load of TEG in the form of 1.4 Ohm LED lights with a variation speed at 20 Km/h, 25 Km/h and 30 Km/hr. The results showed that the engine speed and position of the TEG modules in the exhaust pipe affecting the electrical potential generated. Similarly. The electric power generated is influenced by a cylinder capacity and speed of motorcycles. Maximum electrical power at 110 cc engine is 0.5 W at a speed of 30 Km/h generated smaller than 150 cc engine of 1.2 W at the same speed.